1995
DOI: 10.1111/j.1745-6584.1995.tb00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Observed Migration of a Controlled DNAPL Release by Geophysical Methods

Abstract: Seven hundred seventy liters of a dense nonaqueous phase liquid (DNAPL), tetrachloroethylene (PCE), were released into an isolated volume of a completely saturated natural sandy aquifer. The release was monitored over a period of 984 hours with a variety of geophysical methods including ground penetrating radar, time domain reflectometry, in situ resistivity, and a neutron soil moisture probe. The PCE formed a pool on a low permeability layer at approximately 1 m depth and spread over an area exceeding 32 m2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(79 citation statements)
references
References 16 publications
3
76
0
Order By: Relevance
“…25 The aquifer consist of primarily horizontal, discontinuous lenses of medium grained, fine-grained, and silty fine-grained sand 26 with a mean porosity of 0.33 (n = 36; standard deviation (SD) of 0.017). 27 Despite the observed variability, the sandy aquifer is considered as relatively homogeneous.…”
Section: Methodsmentioning
confidence: 99%
“…25 The aquifer consist of primarily horizontal, discontinuous lenses of medium grained, fine-grained, and silty fine-grained sand 26 with a mean porosity of 0.33 (n = 36; standard deviation (SD) of 0.017). 27 Despite the observed variability, the sandy aquifer is considered as relatively homogeneous.…”
Section: Methodsmentioning
confidence: 99%
“…Borden (Ontario, Canada), where many experiments have been performed with DNAPLs. These experiments have shown that, after its injection, DNAPL is distributed horizontally, forming pools on the horizontal layers with lowest conductivity and vertical trails where the DNAPL free-phase passed during its descent (Kueper et al, 1993 andBrewster et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The first two techniques are active, in that they require electrical current to be injected into the earth; selfpotential is passive, and uses naturally occurring electrical potentials. Other geophysical techniques used to monitor contaminant migration in the subsurface include ground penetrating radar and time domain reflectometry (TDR) (Brewster et al 1995). WSRC-STI-2006-00084, Rev Geophysical monitoring techniques require: (1) a conceptual and theoretical framework that supports the method, (2) demonstrated effectiveness, (3) cost-efficient performance, and (4) the ability to be used for a reasonable time period.…”
Section: Geophysical Methods In Monitoring Mnamentioning
confidence: 99%